2010
DOI: 10.1016/j.tvjl.2008.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Use of a stand-alone pressure plate for the objective evaluation of forelimb symmetry in sound ponies at walk and trot

Abstract: a b s t r a c tSubtle lameness in horses may be difficult to diagnose and methods to evaluate lameness objectively are useful when equine clinicians fail to reach a consensus. The aim of this study was to determine whether equine pressure plate measurements are repeatable when used to calculate forelimb loading (peak vertical pressure [PVP], peak vertical force [PVF], vertical impulse [VI]) and symmetry ratios, and to establish if these data are similar to the 'gold standard' force plate values. Since plate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 16 publications
6
48
3
1
Order By: Relevance
“…The vertical force curves at walk and trot, obtained with both measuring systems, showed a similar pattern as reported earlier by Oosterlinck et al (2009). Nevertheless, in the present study the actual PVF recorded with the PP showed a lower maximal value and was recorded somewhat later in the stance phase compared to the FP measurement.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The vertical force curves at walk and trot, obtained with both measuring systems, showed a similar pattern as reported earlier by Oosterlinck et al (2009). Nevertheless, in the present study the actual PVF recorded with the PP showed a lower maximal value and was recorded somewhat later in the stance phase compared to the FP measurement.…”
Section: Discussionsupporting
confidence: 90%
“…However, the combination of a built-in and fixed FP and PP is really only feasibly in an institute or laboratory and is not practical use in a cost-efficient, mobile clinical environment. Solitary PPs, operational without concurrent FP calibration, have been applied in horses (Rogers and Back, 2007;Oosterlinck et al, 2009) and humans (Thijs et al, 2007). However, before kinetic data obtained with a standalone PP can be used clinically, validation of the system for precision (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using the same pressure plate system simultaneously with a force plate reported that the maximal vertical forces recorded by the pressure plate are lower 17. Nonetheless, the accuracy of the system has proven to be acceptable 18, making it possible to use a pressure plate system to detect trends in gait kinetics over time. Furthermore, the measuring frequency (126 Hz) and with that temporal resolution of the pressure plate system used here is relatively low, especially compared to a force plate system.…”
Section: Discussionmentioning
confidence: 99%
“…32. The following kinetic variables were calculated at walk and trot: 1) peak vertical force (PVF), in N/kg; 2) vertical impulse (VI), in Ns/kg; and 3) stance time (ST) in ms. For each set of five trials, all left forelimb (LF) and right forelimb (RF) measurements were averaged and subsequently PVF, VI and ST ratios between both forelimbs were calculated as: %RF = RF/(LF + RF) × 100%.…”
Section: Methodsmentioning
confidence: 99%